Influence Of Work Motivation, Work Conflict And Work Environment On Performance Employees In Pandemi Time Covid-19 - Fikri, Akhyatul; Soedarsa, Herry G (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
The Covid-19 pandemic has disrupted all processes of social and economic life, including companies. Initially the business could run freely, now the company must establish physical distancing, systems shift, and work from home to reduce the spread of the Covid-19 pandemic. New normal itself is a condition of the impact of the global crisis. The purpose of this study was to determine the effect of work motivation, work conflict and work environment on the performance of PTPN VII Bandar Lampung Office employees during the Covid-19 pandemic. This study uses quantitative research methods. Data analysis used multiple linear regression analysis. Based on the results of research and discussion, it can be concluded that work motivation has a positive effect on the performance of PTPN VII Bandar Lampung employees. Work conflict has a negative effect on the performance of employees of PTPN VII Bandar Lampung. The work environment has a positive effect on the performance of PTPN VII Bandar Lampung employees.